Kehidupan Perempuan Perbatasan: Kemiskinan dan Eksploitasi (Kajian Kasus di Perbatasan Jagoi Indonesia-Malaysia Kalimantan Barat) - Rupita Rupita (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
As the situation of poverty in various parts of the world, as well as experienced by the border women who settled in the border area of Jagoi Babang (Indonesia-Malaysia) Regency of Bengkayang West Kalimantan. Poverty and exploitation seem inseparable from the life of women at the border. In this situation they are the most neglected victims. This paper uses a descriptive analysis approach in data management and field findings. The findings of this writing tell the lives of women living in the frontier, where the lives of those who are poor often become victims of exploitation.